From hair to cornea: toward the therapeutic use of hair follicle-derived stem cells in the treatment of limbal stem cell deficiency - Meyer-Blazejewska, Ewa Anna; Call, Mindy K.; Yamanaka, Osamu; Liu, Hongshan; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Kao, Winston W. (Stem Cells, 2011)
Limbal stem cell deficiency (LSCD) leads to severe ocular surface abnormalities that can result in the loss of vision. The most successful therapy currently being used is transplantation of limbal epithelial cell sheets cultivated from a limbal biopsy obtained from the patient's healthy, contralateral eye or cadaveric tissue. In this study, we investigated the therapeutic potential of murine vibrissae hair follicle bulge-derived stem cells (HFSCs) as an autologous stem cell (SC) source for ocular surface reconstruction in patients bilaterally affected by LSCD. This study is an expansion of our previously published work showing transdifferentiation of HFSCs into cells of a corneal epithelial phenotype in an in vitro system. In this study, we used a transgenic mouse model, K12(rtTA/rtTA) /tetO-cre/ROSA(mTmG) , which allows for HFSCs to change color, from red to green, once differentiation to corneal epithelial cells occurs and Krt12, the corneal epithelial-specific differentiation marker, is expressed. HFSCs were isolated from transgenic mice, amplified by clonal expansion on a 3T3 feeder layer, and transplanted on a fibrin carrier to the eye of LSCD wild-type mice (n = 31). The HFSC transplant was able to reconstruct the ocular surface in 80% of the transplanted animals; differentiating into cells with a corneal epithelial phenotype, expressing Krt12, and repopulating the corneal SC pool while suppressing vascularization and conjunctival ingrowth. These data highlight the therapeutic properties of using HFSC to treat LSCD in a mouse model while demonstrating a strong translational potential and points to the niche as a key factor for determining stem cell differentiation.
EVALuna2:21016